Umbilical cord plasma concentrate has beneficial effects on DNA methylation GrimAge and human clinical biomarkers - Clement, James; Yan, Qi; Agrawal, Megha; Coronado, Ramon E.; Sturges, John A.; Horvath, Markus; Lu, Ake T.; Brooke, Robert T.; Horvath, Steve (Aging cell, 2022)
Plasma transfusions are standard treatments to replace missing proteins in people with rare genetic diseases. Prior studies have demonstrated that heterochronic parabiosis has beneficial effects on several tissues of old animals receiving young blood. Human clinical trials are currently underway to investigate whether the infusion of plasma or plasma‐derived factors from young donors can be used to mitigate human age‐related conditions. Here, we use data from a safety study (n = 18, mean age 74) to investigate whether human umbilical cord plasma concentrate (hereinafter Plasma Concentrate) injected weekly (1 ml intramuscular) into elderly human subjects over a 10‐week period affects different biomarkers, including epigenetic age measures, standard clinical biomarkers of organ dysfunction, mitochondrial DNA copy number (mtDNA‐CN), and leukocyte telomere length. This study shows that treatment with plasma concentrate is safe. More than 20 clinical biomarkers were significantly and beneficially altered following the treatments. For example, creatinine was significantly decreased (p = 0.0039), while estimated glomerular filtration rate (eGFR) was increased (p = 0.0044), indicating the treatment may improve biomarkers of kidney function. Three of four immunoglobulin biomarkers decreased, while telomere length and mtDNA‐CN were not significantly affected by the treatment. The treatment reduced DNA methylation‐based GrimAge by an average of 0.82 years (p = 0.0093), suggests a reduction in morbidity and mortality risk. By contrast, no significant results could be observed for epigenetic clocks that estimate chronological age. Our results support the view that plasma concentrate contains youth‐promoting factors. We conducted a safety study (n = 18, mean age 74) by injecting human umbilical cord plasma concentrate (hereinafter Plasma Concentrate) weekly (1 ml intramuscular) into elderly human subjects over a 10‐week period. Our results indicate that treatment with plasma concentrate is safe. In addition, the treatment reduced DNA methylation‐based GrimAge, suggesting a reduction in morbidity and mortality risk. Taken together, our results support the view that plasma concentrate contains youth‐promoting factors.